2013
DOI: 10.1016/j.jag.2011.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variability in remotely sensed land surface temperature, and its relationship with physiographic variables in the Russian Altay Mountains

Abstract: Spatio-temporal variability in energy fluxes at the earth's surface implies spatial and temporal changes in observed Land Surface Temperatures (LST). These fluxes are largely determined by variation in meteorological conditions, surface cover and soil characteristics. Consequently, a change in these parameters will be reflected in a different temporal LST behavior which can be observed by remotely sensed time series. Therefore, the objective of this paper is to perform a quantitative analysis on the parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 74 publications
1
37
1
Order By: Relevance
“…Second, the correlation between day-time LST and elevation is greater in winter months (December to February) and lower in summer (July-August) for all land cover classes; the opposite is observed for night-time LST. Other authors pointed out the greater correlation between night-time LST and elevation with respect to day-time LST [Fu and Rich, 2002;Pouteau et al, 2011;Van De Kerchove et al, 2013], but our results add that this relation is not consistent throughout the year. The scatter plots also show the effect of the vegetation altitudinal distribution on day-time LST; starting in spring and with a maximum in July and August, points are more scattered around the regression line for lower regions where the variety of the land cover types is greater compared to higher areas (see histograms in Fig.…”
Section: Lst and Elevationcontrasting
confidence: 94%
See 3 more Smart Citations
“…Second, the correlation between day-time LST and elevation is greater in winter months (December to February) and lower in summer (July-August) for all land cover classes; the opposite is observed for night-time LST. Other authors pointed out the greater correlation between night-time LST and elevation with respect to day-time LST [Fu and Rich, 2002;Pouteau et al, 2011;Van De Kerchove et al, 2013], but our results add that this relation is not consistent throughout the year. The scatter plots also show the effect of the vegetation altitudinal distribution on day-time LST; starting in spring and with a maximum in July and August, points are more scattered around the regression line for lower regions where the variety of the land cover types is greater compared to higher areas (see histograms in Fig.…”
Section: Lst and Elevationcontrasting
confidence: 94%
“…The forest class has the lowest difference between day and night temperatures due to the cooling effect of forests [Van Leeuwen et al, 2011]; denser vegetation canopies prevent incoming radiation from reaching the surface and increasing the temperature; this effect also combines with a greater amount of evapotranspiration of dense canopies which has a cooling effect [Van Leeuwen et al, 2011]. Other authors reported that non forested areas experience a greater cooling effect at night than forested regions [Goulden et al, 2006;Van Leeuwen et al, 2011;Van De Kerchove et al, 2013] with greater surface temperatures when vegetation gets denser. Finally, the day-night difference shows the greatest values for cropland areas which have a high surface temperature during the day which decreases significantly during the night; this effect can be observed when compared to the non forest class.…”
Section: Lst and Elevationmentioning
confidence: 99%
See 2 more Smart Citations
“…With the addition of geostationary sensors in recent years, the ability to utilise algorithms with a temporal component for land surface temperature (LST) determination has improved. Modelling of the DTC for LST from geostationary images has been undertaken using absolute descriptive models (Göttsche andOlesen, 2001, Jiang et al, 2006), Reproducing Kernel Hilbert Space models (van den Bergh et al, 2006, Udahemuka andBergh, 2008), Fourier analysis (van de Kerchove et al, 2013), Artificial Neural Networks (Voyant et al, 2014) and Kalman filtering (Masiello et al, 2013, van den Bergh et al, 2009). Utilisation of a single value decomposition (SVD) method, such as that proposed in (Black and Jepson, 1998), has been applied by (Udahemuka and Bergh, 2008) and extended by (Roberts and Wooster, 2014) as part of a robust matching algorithm with significant improvements in the ability to handle temperature anomalies in the observation data.…”
Section: Land Surface Temperature Determinationmentioning
confidence: 99%